Synthesis of Silica nanoparticles from incinerated coconut shell for heavy metal removal - Maathiniyaar Arumugam (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To synthesis the silica nanoparticles using ash from the incinerated coconut shell. To characterize the synthesised silica particles by structural and morphological analyses. To evaluate the adsorption of silica nanoparticle for heavy-metal removal in copper (II) sulphate solution.